Fiscal Stabilization and Growth : Evidence from Industry-level Data for Advanced and Developing Economies - Choi, Sangyup; Furceri, Davide; Jalles, Joao Tovar (Washington, D.C. : International Monetary Fund, 2017)
Medium-term growth can be enhanced by fiscal stabilization. However, to date, no systematic effort has been made to study the specific channels through which fiscal stabilization affects growth. This paper examines the effect of fiscal stabilization on industrial growth and how this effect depends on different technological characteristics. It does so by applying a difference-in-difference approach to an unbalanced panel of 22 manufacturing industries for 55 advanced and developing economies over the period 1970-2014. The results suggest that fiscal stabilization fosters growth in industries with: i) higher external financial dependence and lower asset fixity; ii) higher degree of labor intensity; iii) higher investment lumpiness and relationship-specific input usage. These effects tend to be larger during economic recessions. The results are robust to different measures of fiscal stabilization and the inclusion of various interactions between a broad set of macroeconomic variables and production technologies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet